1971
DOI: 10.1136/sti.47.4.226
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-ophthalmological study of late yaws and pinta. II. The Caracas project.

Abstract: Medina. Approximately forty patients a day were Received for publication January 5, 1971 examined for 3 days. At the suggestion of the epidemiologist, the patients were numbered from 150 to 272, so that the memorizing of numbers would be reduced to a minimum. The studies performed on each patient are listed below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Although infected baboons showed no signs of infection, the treponemes isolated from these animals were able to infect hamsters (Fribourg-Blanc and Mollaret, 1969). Moreover, experimental infection, using humans, revealed that humans could also be infected (Smith, 1971; Smith et al, 1971). A close relationship between the Fribourg-Blanc treponemes and TPE strains has been found by Gray et al (2006), based on the phylogeny of the tprC and tprI genes.…”
Section: Genetic Differences Between Human T Pallidum Subspecies mentioning
confidence: 99%
“…Although infected baboons showed no signs of infection, the treponemes isolated from these animals were able to infect hamsters (Fribourg-Blanc and Mollaret, 1969). Moreover, experimental infection, using humans, revealed that humans could also be infected (Smith, 1971; Smith et al, 1971). A close relationship between the Fribourg-Blanc treponemes and TPE strains has been found by Gray et al (2006), based on the phylogeny of the tprC and tprI genes.…”
Section: Genetic Differences Between Human T Pallidum Subspecies mentioning
confidence: 99%
“…The T. pallidum subspecies and the Fribourg-Blanc treponeme are morphologically indistinguishable by immunofluorescence or electron microscopy (9,14,19,31) and induce similar histopathological changes and cross-reactive antibodies, indicating a high level of antigenic relatedness (3,4,10,12,14,27,30,33,34,36,37). We have earlier reported a singlebase-pair change in the 5Ј-flanking region of the tpp15 gene (6), which introduces an Eco47III restriction site and permits the differentiation of T. pallidum subsp.…”
mentioning
confidence: 99%
“…It affects various species of primates, and its geographical distribution overlaps with regions where yaws is endemic in Western Africa (13). In 1971, Smith et al showed that the Fribourg-Blanc treponeme is able to experimentally infect humans and to cause active infection (34).…”
mentioning
confidence: 99%
“…The Fribourg-Blanc treponeme was isolated from an African baboon with no signs of clinical infection. Little is known about the pathogenesis of the infection (20); however, experimental inoculations showed that this organism is able to produce an active infection in humans (58,59). Rabbit venereal syphilis (caused by T. paraluiscuniculi) is a milder infection characterized by slightly elevated, scaly patches or eroded sores in the genitals, the anus, and, less frequently, the eyelids, lips, and paws of the animals (15).…”
mentioning
confidence: 99%